Racial and Ethnic Disparities in Utilization of Tonsillectomy among Medicaid-Insured Children - Pecha, Phayvanh P. (J Pediatr, 2021)
OBJECTIVE: To examine racial differences in tonsillectomy ±adenoidectomy (T&A) for sleep-disordered breathing (SDB) among Medicaid-insured children. STUDY DESIGN: Retrospective analysis of the 2016 MarketScan Multistate Medicaid Database was performed for children ages 2 to <18 years with a diagnosis of SDB. Patients with medical complexity and infectious indications for surgery were excluded. Racial groups were categorized into non-Hispanic White, non-Hispanic Black, Hispanic, and Other. Adjusted multivariate logistic regression was used to determine if race/ethnicity was a significant predictor of obtaining T&A, PSG, and time to intervention. RESULTS: There were 83,613 patients with a diagnosis of SDB that met inclusion criteria, of which 49.2% were female with a mean age of 7.9 ± 3.8 years. The cohort consisted of White (49.2%), Black (30.0%), Hispanic (8.0%), and Other (13.2%) groups. Overall, 15.4% underwent T&A. Black (82.2%) and Hispanic (82.3%) children had significantly higher rates of no intervention and White patients had the lowest rate of no intervention (76.9%; P < .0001) and the highest rate of T&A (18.7%; p<0.0001). Mean time to surgery was shortest in White compared with Black children (p<0.0001). Logistic regression adjusting for age and sex showed that Black children had 45% reduced odds of surgery (95% CI: 0.53–0.58), Hispanic 38% (95% CI: 0.58–0.68), and Other 35% (95% CI: 0.61–0.70) compared with White children with Medicaid insurance. CONCLUSIONS: Racial and ethnic disparities exist in the utilization of T&A for children with SDB enrolled in Medicaid. Future studies that investigate possible sources for these differences and more equitable care are warranted.